Effectiveness of an educational program for mid‐level Japanese public health nurses to improve program planning competencies: A preliminary randomized control trial. Issue 3 (5th February 2019) - Yoshioka‐Maeda, Kyoko; Shiomi, Misa; Katayama, Takafumi; Hosoya, Noriko; Kuroda, Mariko
Abstract: Objective: To evaluate the effectiveness of an education program for mid‐level Japanese public health nurses (PHNs) to improve their competencies in program planning, which will fulfill community health needs. Design: Randomized control trial. Sample: During 2017, 103 PHNs with 5–20 years of PHN work experience in Japan were enrolled and randomly allocated to the intervention ( n  = 51) or control group ( n  = 52). Measurements: The primary outcome measured competency in program planning based on Competency Measurement of Creativity for PHNs (CMC), knowledge, and skills regarding program planning. Intervention: Six web‐based learning modules followed by two face‐to‐face group sessions. Results: The PHN participants averaged about 12 years of experience. In the intervention group, 25 PHNs completed all modules (49.0%). Post intervention, there were no statistically significant differences among any between‐group CMC scores. However, the intervention group's CMC 3 score was significantly higher than that of the control group of ≥12 years of experience. Total knowledge and skill scores also improved significantly in the intervention group compared with the control group. Conclusions: The results suggest that PHNs with ≥12 years of experience are a suitable target of this educational program, and should play a key role in program planning.